Galerija Cukrarna - Strmole, Blaž (Gradbeni vestnik, 2018)
The old sugar factory building "Cukrarna" in Ljubljana is an important monument of industrial architecture of the 19th century. In the past, there have been several attempts of its renovation and reconstruction, however complete rehabilitation of the whole building has never been carried out. The reconstruction project of the new art gallery building includes the demolition of all the interior walls and roofs, stiffening of the peripheral walls with reinforced concrete cover, implementation of new steel structure of the roofs and floors, reinforcement of foundations and the implementation of new basement.
Keywords: Cukrarna; cultural heritage; galerija; kulturna dediščina; monument; reconstruction; rekonstrukcija; renovation; sanacija; spomenik; sugar factory